Secondary protons in the atmosphere at different latitudes - van Bui, N. A. [UNESP]; Martin, I. M.; Stozhkov, Yu I.; Fradkin, M. I.; Svirzhevskaya, A. (Springer Nature, 1993)
We present a semiempirical method to study the production and propagation of atmospheric secondary protons with energy>100 Mev, moving in the vertical direction. The derived production functions are fitted by the least-square method for the only previously published splash (SP) and return (RE) albedos observed data using the same instrument and measurement sites. The closed agreements between the measurement data and the calculations over a wide range of atmospheric depths lead to a possible extension of the method for other latitudes. The spectra of SP and RE intensities versus the geomagnetic cut-off reveal similar behaviour as assumed earlier by the theory for those components in the Earth's magnetic field. © 1993 Società Italiana di Fisica.
Keywords: Cosmic-ray interactions with the Earth